(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper explores how business activities can pose risks to national security, with a focus on Lithuania and the European Union. It analyzes how illicit practices, foreign ownership, and technological vulnerabilities contribute to threats in areas such as economic security, cybersecurity, and political influence. The research uses a qualitative approach, reviewing legal frameworks, national strategies, and real-world cases, including the revocation of UAB Foxpay’s license and companies with ties to Russia and Belarus. These cases show how business links to authoritarian regimes, when left unchecked, can compromise critical infrastructure and sensitive data, or influence political decision-making. Technological advancements, such as artificial intelligence, digital finance, and global supply chains, increase vulnerabilities. Cases like Huawei and Kaspersky Lab illustrate the persistent risks of espionage, while supply chain attacks show how cyber threats can spread through business networks. The misuse of technology and lack of internal controls in some companies further exacerbate these risks. At the EU level, strategies such as the Security Union Strategy, the Digital Services Act, and the Chips Act aim to strengthen resilience, protect critical sectors, and regulate foreign influence. National measures, including Lithuania’s investment screening and cybersecurity policies, complement these efforts by safeguarding strategic infrastructure and enhancing oversight. The study concludes that protecting national security in a digital and globalized economy requires a collaborative approach. Strong legal regulation must be combined with responsible business conduct. Security begins with knowing your partners and addressing indirect ties that may present risks. Ongoing legal development and consistent enforcement are essential to prevent business-related threats and maintain national stability.